Frontal lobe involvement in the processing of meaningful auditory stimuli develops during childhood and adolescence - Bender, Stephan; Oelkers-Ax, Rieke; Resch, Franz; Weisbrod, Matthias (NeuroImage, 2006)
Auditory event-related N1b reflects attention-related processing in bilateral temporal auditory cortex. Frontal contributions indicating an orienting reaction have been suggested. We analyzed the maturation of frontal contributions to the auditory event-related potential following the warning stimulus in a contingent negative variation (CNV) task by high-resolution current source density mapping and spatio-temporal source analysis in 80 healthy subjects and 121 primary headache patients (migraine with/without aura, tension type headache) from 6 to 18 years; as increased orienting responses and disturbed maturation have been described in migraineurs. A selective local increase of N1b with age occurred at mid-frontocentral leads. This increase could not be explained sufficiently by overlapping bilateral temporal sources but pointed towards additional frontal activation over the supplementary motor area (SMA) in adolescents which was absent in children. A second frontal N1 component peaked about 50 ms later, showed an earlier maturation and has been suggested to reflect early response selection processes in the anterior cingulate. Primary headache patients showed the same component structure and developmental trajectory as healthy subjects without significant influences of differential diagnosis. We conclude that: (1) Brain maturation crucially influences N1b. (2) Two frontal lobe N1 components can be dissociated in their maturational trajectory. (3) Early SMA activation could be elicited by rare auditory stimuli from about 12 years on, allowing fast sensory-motor coupling without previous categorical stimulus classification. (4) Primary headache patients did not differ in their maturation of frontal or temporal contributions to N1b when elicited by moderately loud short tone bursts.
Gesehen am 14.12.2021